The effect of financial ratio and good corporate governance on stock price with company value as a moderation variable in technology companies - Marwah Dian Lailliyah*; Sulastiningsih Sulastiningsih (Universitas Syiah Kuala, 2023)
This research aims to analyze the effect of financial ratios and good corporate governance on stock prices with firm value as moderating variables of technology companies listed on the Indonesia Stock Exchange for 2019-2021. This research uses a quantitative method, with 60 financial reports as samples. The data analysis method used is a descriptive statistical test, classic assumption test, multiple linear regression, and MRA interaction test. The dependent variables in this research return on assets, current Ratio, Ln Assets, and board size, while stock prices are used as independent variables and price to book value as moderating variables. This research concludes that profitability and firm size significantly and partially positively affect stock prices. Liquidity and good corporate governance have a positive but insignificant effect on stock prices. But, simultaneously, profitability, liquidity, firm size, good corporate governance, and firm value impact stock prices. As a moderating variable, substantial value can moderate the effect of profitability and good corporate governance on stock prices. However, it needs to reconcile the impact of liquidity and firm size on stock prices.